Peran Likuiditas Sebagai Pemoderasi Pengaruh Leverage dan Pertumbuhan Penjualan Terhadap Penghindaran Pajak - Purbolakseto, Hengky Veru; Ricky Rudianto, Nur Ahmad (Forum Kerjasama Pendidikan Tinggi, 2024)
This research aims to test whether Leverage and sales growth have an effect on Tax Avoidance and test whether liquidity moderates the effect of Leverage and sales growth on Tax Avoidance. Panel data regression analysis of 189 company years was carried out. The results of this study show that leverage and sales growth have no effect on tax avoidance. By conducting a Moderated Regression Analysis (MRA) analysis, liquidity is a potential moderating variable that is able to moderate or provide an influence in the form of strengthening or weakening the influence of leverage and sales growth on tax avoidance.